BAGAN PENGERINGAN DEHUMIDIFIKASI BEBERAPA JENIS KAYU INDONESIA - Syarif Hidayat (Jurnal Penelitian Hasil Hutan, 1991)
Since it• commercial introduction in the late 1960 deh~midification haa become a  very popular method of dryift6. npeciany  for the •mailer operation drying hardwoods. Dehumidification haa also beenpractiaed in tome lndonaian  mw- milla. However, the  Information concerning the  drying achedule of lndoneaian woods were .till  limited. Thia report'Yi dacribe   the dehumidification drying  achedule for tome lndonaian   commercial woods, •which  were taken from Riau, Lampu"I  and Central Kalimantun. The method uaed in determining the d,.Ying achedule waa adapted from the method ulied by Teruawa  (1966) and Kadir (1976). The experiment were conducted in two ataga. The !ht   atage wa1 preliminary dryinf  to praume  the dryfnl propatie1, and the •cond  atage waa the dryinl  in dehumidifier to identify the real drying 1cheduk.  The  result of  the experiment indicated that the •21  wood apecie• can be classified into three drying achedule, achedule I for wood which it euat    to dry,achedule II moderate and schedule Ill  for the wood with the moat difficult to dry.